Dynamics of Audit Quality: The Effect of Audit Delay, Company Size, And Audit Tenure with The Role of Audit Fee Moderation - Agus Arwani; Muhamad Masrur; Nazia Adeel (AL-FALAH : Journal of Islamic Economics, 2025)
Purpose: This study aims to examine the effect of audit delay, company size, and audit tenure on audit quality, with audit fees acting as a moderating variable, specifically in sharia-compliant firms listed on the Jakarta Islamic Index 70 (JII 70) during 2020–2024. Design/Method/Approach: The research employs a quantitative explanatory approach using secondary data from company financial statements. Audit quality is proxied by the engagement of Big Four auditors, while audit delay, firm size, and audit tenure serve as independent variables. Moderation regression analysis is applied to evaluate the moderating role of audit fees in these relationships. Findings: The results indicate that audit delay, company size, and audit tenure do not significantly influence audit quality, and audit fees do not significantly moderate these relationships. These findings suggest that traditional predictors of audit quality may be less impactful in sharia-compliant firms, possibly due to their strong adherence to Islamic principles emphasizing accountability and transparency. Originality/Values: This study contributes to the auditing and corporate governance literature in Islamic capital markets by highlighting the unique context of sharia-based firms. It provides practical insights for firms and policymakers to enhance audit practices through strengthened internal controls and clearer reporting frameworks.